2016
DOI: 10.4103/0972-6748.196045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of comorbid anxiety disorders in schizophrenia

Abstract: Background:Diagnostic and treatment hierarchical reductionisms have resulted in an oversight of anxiety syndromes in schizophrenia.Aim:The aim of this study was to find the prevalence of different anxiety disorders in schizophrenia patients.Materials and Methods:The study was conducted on inpatients of a tertiary care psychiatric hospital using a prospective, purposive sampling technique. The study consisted of 93 schizophrenia patients and a similar number of normal controls. The schizophrenia patients and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In particular, over half of the clients in this study were found to have clinical depression at baseline and over two thirds had clinical anxiety at baseline. The high prevalence of depressive and anxiety symptoms among the clients may be probably due to the fact that about half of them had already received a diagnosis of depression, anxiety, or bipolar affective disorder and that depressive and anxiety symptoms were common among people with schizophrenia (Aladashvili, 2016;Kiran & Chaudhury, 2016).…”
Section: Discussion and Application To Practicementioning
confidence: 99%
“…In particular, over half of the clients in this study were found to have clinical depression at baseline and over two thirds had clinical anxiety at baseline. The high prevalence of depressive and anxiety symptoms among the clients may be probably due to the fact that about half of them had already received a diagnosis of depression, anxiety, or bipolar affective disorder and that depressive and anxiety symptoms were common among people with schizophrenia (Aladashvili, 2016;Kiran & Chaudhury, 2016).…”
Section: Discussion and Application To Practicementioning
confidence: 99%
“…However, cognitive symptoms are subtle and are often detected only when neuropsychological tests are performed [166]. The prevalence of GAD was significantly higher in patients with SCZ and the prevalence of panic disorder, social anxiety disorder and obsessive-compulsive disorder was significantly higher in SCZ patients [167] (Table 2).…”
Section: Schizophreniamentioning
confidence: 99%
“…However, cognitive symptoms are subtle and are often detected only when neuropsychological tests are performed [165]. The prevalence of GAD was significantly higher in patients with SCZ and the prevalence of panic disorder, social anxiety disorder, and obsessive-compulsive disorder was significantly higher in SCZ patients [166] (Table 2).…”
Section: Schizophreniamentioning
confidence: 99%